1992
DOI: 10.1577/1548-8675(1992)012<0474:mhsbas>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Movement, Habitat Selection, Behavior, and Survival of Stocked Muskellunge

Abstract: High poststocking mortality of muskellunge Esox masquinongy has long been an important management problem. This paper documents poststocking dispersal and subsequent movement, habitat selection, behavior, and survival of fall stocked young‐of‐the‐year muskellunge (12.1–13.1 in total length) with the objective of providing insights into the mechanism controlling short‐term survival. Radio transmitters were surgically implanted into 27 muskellunge that were then stocked with untagged muskellunge into two norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 8 publications
2
40
0
Order By: Relevance
“…No data were used until 8 days after surgery, to enable the fish to become accustomed to the transmitters (Clapp et al 1990;Markham et al 1991). Similarly to other studies (Hanson and Margenau 1992), much movement was observed during the first 3-4 days after release; this subsequently declined to levels typical of the remainder of the study period. Seasonal variation of temperature selection among muskellunge stocks was assessed by defining seasons as spring (15 March-14 June), summer (15 June-14 September), and fall (15 September-14 December) (Burrell et al 2000).…”
Section: Fish Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…No data were used until 8 days after surgery, to enable the fish to become accustomed to the transmitters (Clapp et al 1990;Markham et al 1991). Similarly to other studies (Hanson and Margenau 1992), much movement was observed during the first 3-4 days after release; this subsequently declined to levels typical of the remainder of the study period. Seasonal variation of temperature selection among muskellunge stocks was assessed by defining seasons as spring (15 March-14 June), summer (15 June-14 September), and fall (15 September-14 December) (Burrell et al 2000).…”
Section: Fish Locationsmentioning
confidence: 99%
“…Transmitter frequency was used to identify individual fish. After establishing the general location of the fish, final positions were determined from signal strength by use of a 27 cm whip antenna (Hanson and Margenau 1992;Zigler et al 2003). Preliminary trials indicated that transmitters could be located within a 2 m radius by use of this method.…”
Section: Fish Locationsmentioning
confidence: 99%
“…Although previous work has investigated movement, home range and habitat selection behaviours of mature muskellunge, Esox masquinongy Mitchill (Crossman 1977; Minor & Crossman 1978; Miller & Menzel 1986a,b; Strand 1986; Hanson & Margenau 1992; Margenau 1994), similar information for juvenile muskellunge is lacking. Only Hanson and Margenau (1992) evaluated juvenile muskellunge movement, focusing on initial movements following autumn stocking of age‐0 fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous work has investigated movement, home range and habitat selection behaviours of mature muskellunge, Esox masquinongy Mitchill (Crossman 1977; Minor & Crossman 1978; Miller & Menzel 1986a,b; Strand 1986; Hanson & Margenau 1992; Margenau 1994), similar information for juvenile muskellunge is lacking. Only Hanson and Margenau (1992) evaluated juvenile muskellunge movement, focusing on initial movements following autumn stocking of age‐0 fishes. Knowledge of juvenile movement behaviours is critical to a more complete understanding of a species’ ecology, as behaviours have been shown to differ across life stages in other fishes (McCauley & Huggins 1979; Smith & King 2005; Slavik et al.…”
Section: Introductionmentioning
confidence: 99%
“…Due to loss of habitat, natural recruitment of Muskellunge does not occur in many systems, and populations are maintained entirely through stocking (Wahl 1999). Muskellunge frequently use littoral CWH throughout the year (Hanson and Margenau 1992;Newbrey et al 2005;Wagner and Wahl 2011), and CWH in these systems may provide stocked Muskellunge refuge from predation and enhanced foraging opportunities, which may increase survival rates (Szendrey and Wahl 1996). However, how CWH complexity influences Muskellunge habitat use is unknown.…”
mentioning
confidence: 99%